Fragmentation of arid and semi-Arid ecosystems: Implications for people and animals - Hobbs, N.T.; Reid, Robin S.; Galvin, K.A.; Ellis, J.E. (Springer, 2008)
Human action has modified the earth in many ways, but one of the most pervasive effects of humans on the environment is dissection of natural systems into spatially isolated parts, a process generally known as fragmentation. Fragmentation of environments is not only caused by humans; dynamic natural processes like landslides, fires, and floods can create barriers that dissect natural systems. Understanding the consequences of humancaused and natural sources of fragmentation has been a fundamental challenge in ecology, a problem occupying theoretical and empirical workers for decades (see reviews of Usher 1987, Andren 1994, Collinge 1996, Turner 1996, Young et al. 1996, Harrison and Bruna 1999, Debinski and Holt 2000, Niemela 2001, Chalfoun et al. 2002, de Blois et al. 2002, Schmiegelow and Monkkonen 2002). Moreover, anthropologists and other social scientists have worked to understand the human forces that drive fragmentation of landscapes (Khazanov 1984, Little and Leslie 1999, Kerven 2003). Despite these efforts, understanding of the consequences of landscape fragmentation for human economies and social systems remains rudimentary.